The IndONEsia ICCU Registry - Juzar, Dafsah Arifa; Bagaswoto, Hendry Purnasidha; Muzakkir, Akhtar Fajar; Habib, Faisal; Astiawati, Tri; Prasetya, Indra; Wirawan, Hendy; Ilhami, Yose Ramda; Djafar, Dewi Utari; Sungkar, Safir; Danny, Siska Suridanda (The Indonesian Heart Association, 2023)
Introduction: Patients in the Intensive Cardiovascular Care Unit (ICCU) often present with cardiovascular disease (CVD) issues accompanied by various non-cardiovascular conditions. However, a widely applicable scoring system to predict patient outcomes in the ICCU is lacking. Therefore, developing and validating scores for predicting ICCU patient outcomes are warranted. The aims of the IndONEsia ICCU (One ICCU) registry include developing an epidemiological registry of ICCU patients and establishing a multicentre research network to analyse patient outcomes. Methods and results: This nationwide multicenter cohort protocol will capture data from patients receiving cardiovascular critical care treatment in 10 Indonesian hospitals with ICCU facilities. Recorded data will encompass demographic characteristics, physical examination findings at hospital and ICCU admission, diagnoses at ICCU admission, therapy, intervention, complications on days 3 and 5 of in-ICCU care, in-hospital outcomes, and 30-day outcomes. Conclusion: The One ICCU is a large, prospective registry describing the care process and advancing clinical knowledge in ICCU patients. It will serve as an investigational platform for predicting the mortality of ICCU patients.